International Expansion and the Choice of Foreign Entry Mode: An Analysis of Western European Banks Entry to Baltic and Polish Markets - Vaher, Henri (2007)
This dissertation thesis focuses on the issues of internationalization and foreign expansion. As increasing globalization has made the internationalization more widespread all over the world, the issues of internationalization have found more attention in academic literature. This dissertation tried to test the factors considered to be important in influencing the decision to foreign expansion as well as the choice of foreign entry mode in the banking industry following the process how banks from Western European countries have entered Baltic-Polish region. Theories considered included internationalization stages theory (Uppsala model), resource-based view, transaction cost advantage theory, organizational capabilities theory and number of other theories and concepts.